2022
DOI: 10.1016/j.adro.2021.100869
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Results of Uveal Melanoma Treated With Iodine-125 Plaques: Analysis of Disease Control and Visual Outcomes With 63 Gy to the Target Volume

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…The standard COMS TG-43U calculations assume a homogenous water environment and do not account for a higher attenuation in the silastic material, and it has been shown that this can lead to a dose approximately 10% higher than calculated in a non-water attenuating material [ 23 , 24 ]. Our initial clinical outcomes with 63 Gy prescription with EP plaques was recently published [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard COMS TG-43U calculations assume a homogenous water environment and do not account for a higher attenuation in the silastic material, and it has been shown that this can lead to a dose approximately 10% higher than calculated in a non-water attenuating material [ 23 , 24 ]. Our initial clinical outcomes with 63 Gy prescription with EP plaques was recently published [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Decreasing dose to critical structures in the eye while maintaining margin coverage, especially for tumors near the optic nerve, is a topic of clinical interest, and has been attempted in the past by techniques including modifying COMS plaques [12], using differently designed plaques [13,14], and decreasing prescription doses [15][16][17][18]. Non-uniform loading to decrease dose to organs at risk (OARs) has been investigated with the use of COMS plaques [19], but due to significant dosimetric differences between COMS plaques and other plaque models, these results may not transfer to other types of eye plaques.…”
Section: Purposementioning
confidence: 99%
“…The outcomes from this 63 Gy dose level with this planning paradigm has since been published. 39 These more realistic dose distributions calculated in PS provides two types of dose histogram structures.The histogram primarily used in plan analysis and comparison is the Retinal Dose Area Histogram (RDAH). This is more useful because most structures of interest in the eye are located in its choroidal and retinal layers.…”
Section: Plaque Simulator Eye Model Image-based Planning Rdah/dvh And...mentioning
confidence: 99%
“…Figure 7 shows how prescribing to the tumor apex might not provide margin coverage. The outcomes from this 63 Gy dose level with this planning paradigm has since been published 39 …”
Section: Introductionmentioning
confidence: 99%